2019
DOI: 10.1080/16878507.2019.1617553
|View full text |Cite
|
Sign up to set email alerts
|

Normal abdominal aorta diameter on abdominal sonography in healthy asymptomatic adults: impact of age and gender

Abstract: The study aims to establish the normal criterion of abdominal aortic diameters measured on abdominal sonography based on gender and age, and to study the variation in aortic diameters with age, sex, and height. In this cross-sectional study, a total of 110 asymptomatic adults were examined by ultrasound using 3.5 MHz probes. The diameters of the abdominal aorta were measured at three levels. The results were analyzed using Student's t-test and analysis of variance (ANOVA) on SPSS version 23. The anteroposterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
(12 reference statements)
1
9
1
Order By: Relevance
“…Unfortunately, the retrospective nature of this study only enabled access to sex and age group of the patients examined, which meant that it was only possible to confirm that the diameter of the aorta was larger in men and that it increased progressively with age in both sexes (Figure 18). Several published articles have shown that the diameters of the aorta are larger in men than in women, 12,[18][19][20]22,25,26 but did not determine that the dilation index of these diameters is greater among men than among women in all age groups, as was detected in the present study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Unfortunately, the retrospective nature of this study only enabled access to sex and age group of the patients examined, which meant that it was only possible to confirm that the diameter of the aorta was larger in men and that it increased progressively with age in both sexes (Figure 18). Several published articles have shown that the diameters of the aorta are larger in men than in women, 12,[18][19][20]22,25,26 but did not determine that the dilation index of these diameters is greater among men than among women in all age groups, as was detected in the present study.…”
Section: Discussioncontrasting
confidence: 82%
“…It is of interest to note that the study detected a greater tendency in men to dilation of arteries as age advances, such as the abdominal aorta and RCIA, as has been suggested before in other studies. [17][18][19][20][21][22] The SMA also exhibited greater changes in angle and diameter in men. The lesser predisposition towards changes in arterial anatomy among women may be related to the role played by estrogen, 6,9,22 which increases the bioavailability of nitric oxide (NO) without increasing expression and/or activity of endothelial nitric oxide-synthase (eNOS), which has antioxidant properties that may induce or accelerate vascular aging.…”
Section: Discussionmentioning
confidence: 91%
“…1 ), particularly in local minimum diameters. Comparing the morphological data from this study ( Table 1 ) with similar data for the equivalent arteries shows that this heterogeneity is unique to the venous side ( 26 , 27 ). A likely explanation for this lies in the much lower pressures (5–10 mmHg) ( 28 ), thinner vessel wall, and a high degree of compliance of the vena cava.…”
Section: Discussionsupporting
confidence: 55%
“…It was reported that the diameter of the aorta increases with age. In younger ages, the diameters remains fixed, but with age increase, the diameters of the aorta appears to be significantly affected by age and gender [ 10 , 11 ]. Rylski et al reported that the female gender is associated with smaller aortic dimensions at a young age, which may help protect against aortic dissection.…”
Section: Discussionmentioning
confidence: 99%